Decision of choosing study programs based on students’ perceptions of accounting study programs in Batam - Hamta, Firdaus; Ikhlash, Muhammad; Syuaib, Mustaqim; Santoso, Cahyo Budi (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
This study was aimed to identify the factors of new college students’ perception in choosing an accounting study program in Batam and strategies to develop an accounting study program on increasing the number of incoming new students in Batam. This study was conducted by using descriptive qualitative methods and data collection techniques were done through structured interviews with informants from undergraduate students or equivalent in the first, third, fifth, and seventh semester of the accounting study program in Batam. The main research informants were 34 students of the accounting study program, both of Riau Islands University and Batam State Polytechnic. The results showed that seven main factors in the decision to choose an accounting study program in Batam, namely (1) transportation accessibility; (2) accreditation of study programs; (3) employment; (4) competency program; (5) supporting services and facilities; (6) lecturer education level; (7) tuition fees. The finding of new factors in the decision to choose an accounting study program, namely the educational background of high school/vocational school, social science or accounting.